2017
DOI: 10.1371/journal.pbio.2001992
|View full text |Cite
|
Sign up to set email alerts
|

EBV epigenetically suppresses the B cell-to-plasma cell differentiation pathway while establishing long-term latency

Abstract: Mature human B cells infected by Epstein-Barr virus (EBV) become activated, grow, and proliferate. If the cells are infected ex vivo, they are transformed into continuously proliferating lymphoblastoid cell lines (LCLs) that carry EBV DNA as extra-chromosomal episomes, express 9 latency-associated EBV proteins, and phenotypically resemble antigen-activated B-blasts. In vivo similar B-blasts can differentiate to become memory B cells (MBC), in which EBV persistence is established. Three related latency-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 62 publications
(108 reference statements)
3
74
2
Order By: Relevance
“…EBNA3A and EBNA3C rescue infected cells that are driven into a proliferative state by EBNA2-dependent MYC expression via the down-regulation of the proapoptotic BIM and p16 INK4a proteins that respond to the hyperproliferation of the infected cells 43 . Furthermore, they prevent transition into lytic replication by suppression of BLIMP1 expression 44 . By contrast,…”
Section: Transformation and Oncogenesismentioning
confidence: 99%
“…EBNA3A and EBNA3C rescue infected cells that are driven into a proliferative state by EBNA2-dependent MYC expression via the down-regulation of the proapoptotic BIM and p16 INK4a proteins that respond to the hyperproliferation of the infected cells 43 . Furthermore, they prevent transition into lytic replication by suppression of BLIMP1 expression 44 . By contrast,…”
Section: Transformation and Oncogenesismentioning
confidence: 99%
“…To overcome this barrier, LMP1, EBNA3, and EBV miRNAs each downmodulate Blimp1 (40,55,56). LMP1 upregulates IRF2 and its corepressor IRF2BP2 via EBV SE, which may form repressor complexes at a Blimp1 promoter interferon response element to counteract IRF4 effects on Blimp1 (40).…”
Section: Viral Super-enhancers Target Key Host Dependency Factorsmentioning
confidence: 99%
“…LMP1 upregulates IRF2 and its corepressor IRF2BP2 via EBV SE, which may form repressor complexes at a Blimp1 promoter interferon response element to counteract IRF4 effects on Blimp1 (40). EBNA3A and EBNA3C also block LCL Blimp1 upregulation, and withdrawal of EBNA3A and EBNA3C expression triggered plasma cell differentiation (56). Further studies are required to determine whether LMP1-activated IRF4, BATF4, and perhaps IRF2 tether EBNA3 corepressor complexes at the Blimp1 promoter.…”
Section: Viral Super-enhancers Target Key Host Dependency Factorsmentioning
confidence: 99%
“…It is known that in order to escape the immune surveillance of the host and establish a chronic infection, EBV has evolved different mechanisms to maintain B cells in a status of long-lived circulating memory B cells and prevent them from differentiating into antibody-secreting plasma cells. A recent study showed that EBNA3A and EBNA3C block the terminal differentiation of memory B cells to plasma cells by epigenetically repressing the gene encoding BLIMP-1, a master regulator in B-cell differentiation (33). Notably, a previous study showed that KDM2B plays a key role in the differentiation of hematological stem cells (9).…”
Section: Discussionmentioning
confidence: 99%